Association of high estimated glomerular filtration rate with risk of atrial fibrillation: a nationwide cohort study - Kang, Min Kyoung; Ha, Hee-Jung; Jung, Raon; Oh, YunSeo; Kim, Dong-Hyeok; Song, Tae-Jin (Frontiers in Medicine, 2023)
Aim: While the relationship between impaired kidney function and atrial fibrillation (AF) is well established, there is limited research exploring the association between elevated estimated glomerular filtration rate (eGFR) and AF development. This study aimed to examine the association between higher-than-normal eGFR and AF risk using a nationwide longitudinal study of the general population in Korea. Material and methods: This study utilized the National Health Insurance Service cohort database of Korea, analyzing data from 2,645,042 participants aged 20-79 years who underwent health examinations between 2010 and 2011. Participants with a history of endstage renal disease, renal transplantation, and AF prior to the index date were excluded. Renal function was assessed using eGFR levels, calculated with the Chronic Kidney Disease Epidemiology Collaboration (CKD-EPI) equation. Baseline characteristics were gathered through questionnaires, while comorbidities and AF occurrence outcomes were identified and validated using diagnostic codes and medication histories. The study employed Kaplan-Meier survival curves and Cox proportional hazard models to evaluate the association between eGFR and AF occurrence.Results: The mean age of subjects was 48.82 ± 10.08 years. Over a median follow-up of 9.58 years, 27,469 (1.04%) AF cases were identified. The risk for AF increased in the higher-thannormal decile, as demonstrated by Kaplan-Meier survival curves (p < 0.001). The eGFR < 30mL/min/1.73m 2 group was associated with an increased risk of AF (hazard ratio (HR) 1.22, 95% confidence interval (CI) [1.01, 1.46], p=0.039), while the eGFR > 120mL/min/1.73m 2 group was associated with a decreased risk of AF (HR 0.88, 95% CI [0.78, 0.98], p=0.045).Compared to the 5th decile, the 1st (HR: 1.08, 95% CI [1.03, 1.13], p=0.010) eGFR decile was significantly associated with an increased risk of AF, while the 10th (HR: 0.77, 95% CI [0.70, 0.85], p<0.001) eGFR decile was significantly associated with a reduced risk of AF.The study revealed that individuals with eGFR>120mL/min/1.73m 2 or those falling within eGFR 10th decile (>113.41ml/min/1.73m²) demonstrated an inverse association linked to a reduced risk of AF. Our study suggests that general population with higher-thannormal eGFR levels may have a lower risk of developing AF.